Misja publiczna w telewizji polskiej - Lasota, Tomasz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2013)
The author explains the sense of mission in relation to public television; first, he defines the concept of the public mission in the media, and then explains how Polish Television complies with the obligations imposed on it.